The effects of predictive trials on critical stroke rate and critical swimming speed - Raimundo, J. A.; Ribeiro, G.; Lisbôa, F. D.; Pereira, G. S.; Loch, T.; De Aguiar, R. A.; Martins, E. C.; Caputo, F. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Critical swimming speed (CSS) and critical stroke rate (CSR) have important practical applications in evaluating endurance capacity and stroke parameters. The CSS and CSR are determined from the linear regression between two or more performance times with the respective predictive distance or "number of stroke cycles," respectively. It is already known that CSS is dependent on the number and duration of the predictive trials chosen, and performance times ranging from 2 to 12 min have been recommended. However, the effects of predictive trials on the CSR have not been reported. It was hypothesized that CSS and CSR determined by different predictive trials lasting 2 to 12 min would elicit similar values. Therefore, the purpose of the present study was to determine the impact of different combinations of predictive trials lasting 2 to 12 min on both CSR and CSS. METHODS: Thirteen swimmers performed three fixed-distance (200, 400, and 800 m) performances. All possible combinations of CSR and CSS with two (CSR200-400/CSS200-400, CSR200-800/CSS200-800, CSR400-800/CSS400-800) and three (CSR200-400-800/CSS200-400-800) trials were determined. RESULTS: No significant differences were found between CSR and CSS determined with different predictive distance tests. In addition, CSR200-800 and CSS200-800 showed the lowest coefficient of variation and highest intraclass correlation coefficients with CSR200-400-800 and CSS200-400-800, respectively. CONCLUSIONS: This study demonstrated that CSR and CSS were not statistically different when determined with different predictive trials located within the recommended durations of 2-12 min. Nevertheless, CSR200-800 and CSS200-800 exhibited the best consistency with CSR200-400-800 and CSS200-400-800, respectively.